Career decision-making self-efficacy in relation to career aspirations among junior college one students - Ng, Soo Kok. (2009)
The present study investigated the utility of the career decision-making self-efficacy construct to the understanding and treatment of two important components of career aspiration namely, certainty of career choice and career self-efficacy. The study was applied to Junior College students because they were at the threshold of specifying their career aspirations prior to entering tertiary education. A total of 372 Year One students from three Junior Colleges responded to the Career Decision-Aspiration Questionnaire. The extent and degree of indecision among the student sample with respect to specifying an academic major and occupation were examined through the use of a three-level classification according to self-declared status i.e. students who have decided, who have made tentative selections and who were undecided. Results of ANOVAs and post-hoc analyses on these three groups of students showed that CDMSE scores validly discriminated them ; CDMSE scores were highest among students who had decided on their academic major or occupation, followed by those who had made tentative selection. CDMSE scores were lowest among those who were undecided.